NORMATIVE STUDY OF THE RIGHT TO SPACE IN THE INSTALLATION OF DIGITAL INFRASTRUCTURE - Igo Primantara Ari Putra; Irman Syahriar; Dina Paramitha Hefni Putri; Khairunnisah (Awang Long Law Review, 2025)
This research is entitled Normative Study of the Right to Space in the Installation of Digital Infrastructure, which aims to analyze the legal and justice aspects in the use of space for the development of digital infrastructure in Indonesia. The development of digitalization demands the availability of legal and equitable space for the installation of towers, fiber optic networks, and other supporting devices. In a legal context, the right to space originally focused on physical development, but has now expanded to encompass the need for digital space as a vital public facility. The method used is doctrinal legal research with a statutory and conceptual approach, examining the suitability of legal norms governing the management of physical space as regulated in Spatial Planning Law Number 26 of 2007 and digital. The study results show that the regulation of spatial rights for digital infrastructure must guarantee the principles of legality, social justice, transparency, and public participation. The state plays a central role in regulating and ensuring equal access, data protection, and equitable distribution of digital benefits for all members of society. This research emphasizes the importance of adaptive and equitable digital legal transformation so that infrastructure development does not create disparities, but rather realizes inclusive, safe, and sustainable spatial planning in the era of technological transformation.